2012
DOI: 10.1159/000335499
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal Syndrome Type 1 May Be Immunologically Mediated: A Pilot Evaluation of Monocyte Apoptosis

Abstract: Background: Cardiorenal syndrome (CRS) type 1 is characterized by a rapid worsening of cardiac function leading to acute kidney injury (AKI). An immune-mediated damage and alteration of immune response have been postulated as potential mechanisms involved in CRS type 1. In this pilot study, we examined the possible role of the immune-mediated mechanisms in the pathogenesis of this syndrome. The main objective was to analyze in vitro that plasma of CRS type 1 patients was able to trigger a response in monocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 62 publications
6
39
0
Order By: Relevance
“…In particular, in a recent study [25], they observed that the plasma of CRS type 1 patients induces apoptosis in U937 cells. However, this study had a strong limitation: all 15 patients included with CRS type 1 had CKD prior to their enrollment in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, in a recent study [25], they observed that the plasma of CRS type 1 patients induces apoptosis in U937 cells. However, this study had a strong limitation: all 15 patients included with CRS type 1 had CKD prior to their enrollment in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in previous studies, de Cal and colleagues [27,28] had shown that the plasma of patients with CKD by itself induces apoptosis in these cells. In fact, Virzì et al [25] reported that apoptosis appeared to increase across CKD stages 1-4 and that this was associated with increased proinflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Virzì et al [41] explored the premise of an immune-mediated process in the pathophysiology of this syndrome and showed marked apoptotis in monocytes incubated with CRS type 1 plasma. The specific immune responses during AKI facilitate and enhance distant heart-kidney crosstalk; in particular, inflammation of renal tissue stimulates the expression of adhesion molecules in endothelial cells, which leads to the deposition of immune complexes and vascular stiffening in kidney disease [30].…”
Section: Nonhemodynamic Mechanisms Of Heart-kidney Crosstalk In Crs Tmentioning
confidence: 99%
“…In addition, apoptotic pathways and caspases seem to have direct effects on cardiomyocyte contractility and remodeling, cleaving myocardiac contractile proteins and promoting systolic dysfunction [67,68]. Recent evidence has suggested that immune-mediated mechanisms are implicated in the pathogenesis of CRS type 1 [41,69]. It has been recently shown that plasma from CRS type 1 patients induced apoptosis in monocytes with an activation of caspase cascade; furthermore, IL-6 levels were significantly higher in these patients when compared with healthy controls and heart failure patients without kidney impairment [41,69].…”
Section: Nonhemodynamic Mechanisms Of Heart-kidney Crosstalk In Crs Tmentioning
confidence: 99%
See 1 more Smart Citation